REGULATING SPRING WILD TURKEY HUNTING BASED ON POPULATION AND HUNTING QUALITY - Richard O. Kimmel (Wildlife Society Bulletin)
Abstract: Wildlife managers are challenged to provide sustained harvests and safe, quality hunting experiences. A wide range of factors is considered by wildlife agencies when developing strategies for spring wild turkey (Meleagris gallopavo) hunting seasons. Although hunting males in spring is considered a conservative harvest strategy, factors such as illegal kill of females and excessive harvest of males can affect population levels and age structure. I review population and hunt quality factors considered in setting spring wild turkey hunting seasons and describe a mathematical model that estimates populations and uses population levels and hunting quality indicators to allocate permits for spring wild turkey hunting in Minnesota. The model provides a logical organization of available information for making management decisions. With this model, clientele can clearly see how turkey population data and hunting quality indicators are used in our decision‐making process. The model is conceptually simple and uses readily obtainable information. It is applicable to a wide range of harvest management objectives, including protecting the wild turkey resource and providing quality hunting.